Barriers and Facilitators of Physical Activity for Mental Health Enhancement in University Students (International Journal of Atharva, 2025)
Background: Mental health concerns among undergraduate students have reached critical levels globally, characterized by high rates of anxiety, depression, and stress, a situation exacerbated by recent global crises. In this context, physical exercise has emerged as a significant non-pharmacological intervention, with evidence suggesting its benefits for psychological well-being through neurochemical, cognitive, and social mechanisms. However, barriers such as academic pressure and low motivation often hinder consistent student engagement.Objectives: This study aimed to (1) assess the levels of physical exercise and mental health among undergraduate students, (2) examine the relationship between these two variables, and (3) analyze the impact of physical exercise on students' mental health.Methods: A quantitative cross-sectional study was conducted with 204 undergraduate students from various faculties, selected via convenience sampling. Data were collected using a self-administered questionnaire. Descriptive statistics were used to summarize demographic and response data, while inferential statistics, including Kendall’s Tau-b correlation and simple linear regression, were employed to analyze the relationship and impact between physical exercise (independent variable) and mental health (dependent variable).Findings: A strong majority of students perceived physical exercise as beneficial for managing stress (66.2%), anxiety symptoms (73%), and depressive feelings (67.2%). Correlation analysis revealed a statistically significant, positive relationship between physical exercise and mental health (τ_b = 0.292, p < 0.001). Regression analysis confirmed that physical exercise is a significant predictor of mental health (B = 0.429, β = 0.443, p < 0.001), indicating that increased physical activity is associated with improved mental well-being.Conclusion: The study concludes that physical exercise has a significant positive relationship with and a measurable positive impact on the mental health of undergraduate students. Students themselves recognize the profound psychological benefits of staying active, often valuing them above physical gains.Implication: Universities should proactively integrate accessible, inclusive, and promoted physical activity initiatives into campus life and policy. Designing programs that overcome common barriers to exercise can serve as a powerful public health strategy to enhance student psychological resilience, academic performance, and overall well-being.